Rates of Return on Stocks, Inﬂation and Money Market Returns: An Indonesian Case Study, I980 – 1992 - Manurung, Adler (The International Journal of Accounting and Business Society, 1994)
This paper examines annual rates of return on investment over 1980 - 1992 in Indonesian bank time deposits, the inter-bank money market and stocks (both domestic returns and US Dollar returns) and also risk for these instruments. The results show that most investments had negative correlation with inﬂation and that USD value of investment in the JSE composite index was severely affected by the fall in value of the Rupiah. Keywords: Indonesian Rates of Return, Equity. Inﬂation, Monetary Markets